Effect of Vitamin D3 on Lifespan in Caenorhabditis elegans - A. Messing, Jennifer; Heuberger, Roschelle; A. Schisa, Jennifer (Current Aging Science, 2013)
Vitamin D is an essential micronutrient, necessary for human health. To determine if Caenorhabditis elegans (C. elegans) could function as an effective model to study the mechanisms of action of vitamin D, we asked if vitamin D3 affects C. elegans lifespan. Multiple factors positively impact lifespan in this system including dietary restriction and vitamin E. In addition, the C. elegans DAF-12 nuclear hormone receptor is homologous to the vitamin D receptor in humans and is therefore a candidate for a functional vitamin D receptor. It was hypothesized that vitamin D3 supplementation would increase the lifespan of C. elegans in a DAF-12-dependent manner. Dose-response curves were completed, and results indicate that exposure to 1,000 µg/ml vitamin D3 significantly increased the lifespan of wild-type worms by up to 39% (p<0.001). The daf-12 mutants exposed to 1,000 µg/ml vitamin D3 lived significantly longer than daf-12 controls exposed to 0 µg/ml (p<0.001), but among worms exposed to 1,000 µg/ml vitamin D3, wild type lived significantly longer than daf-12 (p<0.01). The data suggest that vitamin D3 can interact with multiple receptors, possibly implicating the NHR family of nuclear hormone receptors related to DAF-12. This research is the first to our knowledge to utilize C. elegans as a model to study the impact of vitamin D3 on longevity and supports the use of this model system to increase our understanding of vitamin D function at the cellular level, its role in cellular health, and its potential medicinal utility in humans.
Keywords: cholecalciferol